(untitled) (Research, Society and Development, 2024)
Viral hepatitis are infections caused by different etiological agents that have a hepatotropism and are divided into five main types: hepatitis A, B, C, D and E viruses. With a universal distribution and being the second leading cause of death among infectious diseases, viral hepatitis installed as a serious public health problem, not only in Brazil, but worldwide. Objective: this study aimed to evaluate the knowledge that the population of São José dos Campos had about the forms of transmission and prevention of viral hepatitis. Methods: was conducted a cross-sectional, descriptive and quantitative research, based on the application of a questionnaire through the Google Forms platform, which had demographic issues and issues pertinent to viral hepatitis. 160 people answered the survey, however, following the exclusion and inclusion criteria of the study, remaining 121 people. Results: The data revealed that the level of education is linked to a higher level of knowledge about viral hepatitis, concluding that the higher the level of education, the greater the chances of people to have a good knowledge. It was also observed that those who had greater knowledge about the transmission and prevention of these infections, were the participants who knew someone who once had the disease. Conclusion: although most participants had a good knowledge about viral hepatitis, there is still a portion of people who demonstrate a lack of knowledge about the ways of transmission and prevention of these infections.